AFTA: ANTARA DINAMIKA EKONOMI KAWASAN ASEAN DAN TANTANGAN INDUSTRI DOMESTIK INDONESIA - Fadhel, Muhammad; Atman, Wira (Cahaya Ilmu Bangsa, 2024)
AFTA is designed to create deeper economic integration through reducing trade barriers, such as tariffs and non-tariff barriers, in order to strengthen the flow of goods and services between member countries. This has an impact on increasing trade volume, supply chain efficiency and the competitiveness of ASEAN products in the global market. However, AFTA implementation also poses serious challenges, especially for countries with less competitive domestic industries. Cheaper and better-quality imported products tend to shift people's preferences, foster consumerism, while weakening local industry. This study aims to provide strategic insight for policy makers, industry players and the public in understanding the balance between the benefits and risks of regional economic cooperation. AFTA dirancang untuk menciptakan integrasi ekonomi yang lebih mendalam melalui pengurangan hambatan perdagangan, seperti tarif dan hambatan non-tarif, guna memperkuat arus barang dan jasa antarnegara anggota. Hal ini berdampak pada peningkatan volume perdagangan, efisiensi rantai pasokan, dan daya saing produk ASEAN di pasar global. Namun, implementasi AFTA juga menimbulkan tantangan serius, terutama bagi negara-negara dengan industri domestik yang kurang kompetitif. Produk impor yang lebih murah dan berkualitas cenderung menggeser preferensi masyarakat, menumbuhkan sifat konsumtif, sekaligus melemahkan industri lokal.. Studi ini bertujuan untuk memberikan wawasan strategis bagi pembuat kebijakan, pelaku industri, dan masyarakat dalam memahami keseimbangan antara manfaat dan risiko kerja sama ekonomi regional.